The Effectiveness of Free Nutritious Meal Programs in Improving Student Motivation and Achievement in Indonesia: A Sociological Perspective of Education - Azhari Sunni, Marzuki (Yayasan Mentari Madani, 2025)
The Free Nutritious Meal (MBG) Program is one of the strategic policies of the Indonesian government that aims to improve the quality of education through meeting the nutritional needs of students, especially from vulnerable socio-economic groups. This study aims to analyze the effectiveness of the Free Nutritious Meal Program (MBG) in increasing student motivation and achievement in Indonesia from the perspective of educational sociology. This study uses a mixed methods approach with a sequential explanatory design, which combines quantitative and qualitative methods sequentially. Quantitative data was collected through learning motivation questionnaires and documentation of students' academic scores before and after the implementation of MBG, while qualitative data was obtained through in-depth interviews, observations, and analysis of policy documents. The results of the study showed that the MBG Program had a positive and significant effect on increasing students' learning motivation, which was reflected in increased concentration, class participation, and study perseverance. In addition, this program also contributes to improving student learning achievement, although with varying impacts between educational units. From the perspective of the sociology of education, MBG functions as a form of state intervention in providing basic educational support that is able to reduce structural barriers due to socio-economic inequality. This program has been proven to have a redistributive function with a more significant impact on students from underprivileged families. However, the effectiveness of MBG is greatly influenced by the quality of program implementation and governance at the school level. This research emphasizes the importance of integrating education and social policies to realize a more equitable and sustainable education system